2015
DOI: 10.1007/s12026-015-8713-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrative neuroscience approach to neuropsychiatric lupus

Abstract: We present a succinct review of our approach to study the interactions between the DNA-reactive antibodies that cross-react with the GluN2A and GluN2B subunits of the N-methyl-D-aspartate receptor, denoted DNRABs, and their brain targets in subjects with neuropsychiatric systemic lupus erythematosus (NPSLE). We have analyzed the DNRAB-based brain symptomatology in mouse models of NPSLE by using an integrative neuroscience approach, which includes behavioral assessment coupled with electrophysiological studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 77 publications
0
9
0
1
Order By: Relevance
“…There has not been any local or regional study on this topic till date. Cognitive dysfunction has been found to be prevalent in SLE, ranging from 12% to as high as 87% and 95% 3,13. A study from Egypt used MoCA scale and found that 96.6% of patients showed impairment using MoCA scores, but this study was done in patients having lupus nephritis 7.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…There has not been any local or regional study on this topic till date. Cognitive dysfunction has been found to be prevalent in SLE, ranging from 12% to as high as 87% and 95% 3,13. A study from Egypt used MoCA scale and found that 96.6% of patients showed impairment using MoCA scores, but this study was done in patients having lupus nephritis 7.…”
Section: Discussionmentioning
confidence: 86%
“…A total of 43 patients were selected from both outpatient and inpatient departments after sample size calculation (95% Confidence level, 10% margin of error and taking frequency of cognitive dysfunction in Systemic Lupus Erythematosus of 87%) 3,8,13. All these patients fulfilled the 2012 SLICC (Systemic Lupus International Collaborating Clinics) classification criteria for Systemic Lupus Erythematosus and excluded those patients who were unable to read or write and those who had uraemia, sepsis or uncontrolled thyroid disease, as these affect cognition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first systematic review and meta-analysis to compare the cognitive performance of NP-SLE patients with that of nonNP-SLE patients. Cognitive impairment is one of the most prevalent neuropsychiatric presentations in SLE patients (Benedict et al, 2008;Huerta et al, 2015), and although it is well established that cognitive deficits are more severe and extensive in NP-SLE patients than in nonNP-SLE patients (Carlomagno et al, 2000;Mikdashi et al, 2007;Kozora et al, 2008), a specific profile of cognitive deficits affecting this population has not been defined. The literature on this topic is not extensive, and results are inconclusive owing to important methodological limitations across studies, such as failure to clearly describe the criteria used to define patient groups and a lack of explanation of the specific cognitive measures used in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty of Medicine and Nursing, University of the Basque Country, Barrio Sarriena s/n, 48940 Leioa, Bizkaia, Spain. E-mail: arantzazu.zabala@ehu.eus Cognitive impairment is one of the most frequent neuropsychiatric presentations in SLE patients (Ainiala et al, 2001;Benedict, Shucard, Zivadinov, & Shucard, 2008;Huerta, Gibson, Rey, Huerta, & Huerta, 2015). Its prevalence ranges from 14% to 95% across studies, with inconsistencies possibly associated with differences in the characteristics of the patient samples, selection of tests, and classification of impairment (Kozora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%